Struktur dan Fungsi Sosial Cerita Rakyat Legenda Batu Batikam Jorong Dusun Tuo Kecamatan Lima Kaum Kabupaten Tanah Datar - Dasti Meylan Hasanah; Nurizzati (Persona: Kajian Bahasa dan Sastra, 2023)
This study aims to describe: (1) the structure of the folklore of the Batu Batikam legend in Jorong Dusun Tuo, Limo Kaum District, Tanah Datar District. (2) the social function of the folklore of the Batu Batikam legend in Jorong Dusun Tuo, Limo Kaum District, Tanah Datar Regency. This type of research is literary research with descriptive methods. The background, entries, and presence of the researcher is the folklore of the Batu Batikam legend in Jorong Tuo Hamlet, Limo Kaum District, Tanah Datar Regency. Quotations were collected from informants through two stages, namely (1) the recording stage of the Batu Batikam legend folklore (2) the transcription and transliteration stages. (3) data validation stage. (4) data analysis stage. Data was taken by note-taking techniques, observations and interviews. The results of this study are: 1) the structure of the folklore of the legend of Batu Batikam in Jorong Dusun Tuo, Limo Kaum District, Tanah Datar Regency which is divided into, (a) style of language, which is used in the Minangkabau language Ba-tusangkar dialect (b) characters and characterizations, the character Dt. Parpatiah Nan Sabatang and Dt. Katumangguangan (c) setting, place setting in Jorong Tuo Hamlet, Limo Kaum District, Tanah Datar Regency. The time setting is not certain, it is only estimated in ancient times (d) the plot used is advanced (e) the theme, which uses the presence of sacred stones as a symbol of peace and belief in the Minangkabau people. (f) mandate, no matter how serious the problem with anyone is not to hurt other people or injure other people. 2) the social function of the legend of Batu Batikam folklore in Jorong Dusun Tuo, Limo Kaum District, Tanah Datar Regency, which is divided into, (a) entertaining, this story is entertainment for people who are resting, (b) educates, Batu Batikam folklore, this story becomes teaching for many people (c) pass on, this folklore is passed on to children of the next generation (d) identity. For the Limo Kaum people, the legend of batu batikam serves as a social image that reflects cultural norms as well as an effort so that the people there always adhere to these norms.